2022
DOI: 10.1177/07319487221136279
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Explicit Decoding Plus Frequency Building Intervention on Word Reading Fluency for Students With Disabilities in an Urban Elementary Setting

Abstract: Students with disabilities in upper elementary grades who read well below grade level often require one-to-one intensive intervention. The following study examines the effects of a combined explicit decoding plus frequency building intervention on consonant–vowel–consonant (CVC) word reading fluency. Participants included two third-grade students and one fourth-grade student from an urban elementary school receiving special education services. Delivered during the intervention block, the students practiced 5 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…While the improvement in self-concept was slightly larger for the intervention group, the absence of a significant interaction effect suggested that the change over time for both groups was comparable. Hence, the enhancement of students' selfconcept as readers may simply reflect the overall growth observed in both groups, as research shows that these go hand in hand [17,25,27].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…While the improvement in self-concept was slightly larger for the intervention group, the absence of a significant interaction effect suggested that the change over time for both groups was comparable. Hence, the enhancement of students' selfconcept as readers may simply reflect the overall growth observed in both groups, as research shows that these go hand in hand [17,25,27].…”
Section: Discussionmentioning
confidence: 99%
“…This program resulted in a multicomponent reading fluency approach, encompassing techniques like challenging word exploration (focusing on phonological structure and meaning), model reading, eco reading, assisted reading, and both self and hetero assessment of reading abilities. Integrated motivational strategies included praise, effort reinforcement during each reading, timely corrective feedback, and post-assessment goal setting in every session [17,25]. Moreover, the inclusion of self-assessment via audio recordings, allowing students to evaluate facets like text reading accuracy, fluency, and prosody, served as a motivational lever.…”
Section: Intervention Programmentioning
confidence: 99%
See 3 more Smart Citations